Rigid composite materials from olive brush seed and unsaturated polyester resin - Jiménez, L. (2008)
A composite material using unsaturated commercial polyester resin (UPE) and olive brush seed (OBS) was prepared. OBS was treated with sodium hydroxide and maleic anhydride (MAN) and subsequently utilized in a proportion of 35 wt.% to prepare a composite material. These materials were evaluated in terms of moisture absorption, surface density, and mechanical properties such as flexure and tensile tests.